Peran Pemikiran Pendidikan KH. Ahmad Dahlan dalam Pendidikan Muhammadiyah Masa Kini - Salsabila, Dina; Zalnur, Muhammad; Masyhudi, Fauza (ALSYS, 2024)
KH. Ahmad Dahlan, as the founder of Muhammadiyah, laid the foundations of Islamic education thinking that is oriented towards progress and renewal, making education an important means of producing a generation that is moral, knowledgeable, and able to face the challenges of the times. His thinking, which emphasizes the integration of religious and general sciences and the relevance of education to social reality, has become the main foundation of Muhammadiyah education until now. This article aims to examine the role and relevance of KH. Ahmad Dahlan's educational thought in the practice of Muhammadiyah education today, especially in facing the era of globalization and rapid technological development. The research method used is descriptive qualitative through library research. The results of the study show that the renewal values promoted by KH Ahmad Dahlan are still the main principles in the curriculum, learning methods, and vision of Muhammadiyah education. The implementation of this thought can be seen in the efforts of Muhammadiyah schools to produce graduates who are not only academically competent, but also have a strong Islamic personality, social spirit, and are ready to contribute to society. Thus, the thought of KH. Ahmad Dahlan not only provides direction for Muhammadiyah education, but also becomes the foundation in the development of Islamic education in Indonesia.